Factors associated with complications in patients with Intestinal ostomy in the emergency area in 2019, at the Abel Gilbert Pontón hospital (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
Stoma formation is a procedure commonly performed in colorectal surgery as part of operations performed for inflammatory and malignant bowel disease. Stoma formation is a simple but not trivial task. When done poorly, it can leave patients with a legacy of complications such as leakage, prolapse, parastomal hernia, and retraction.Objective: To determine the factors associated with complications in patients with intestinal ostomies in the emergency area of the "Abel Gilbert Pontón" Hospital during 2019.Methodology: Study of a non-experimental, observational, analytical, retrospective and cross-sectional type, which analyzed patients with intestinal ostomies who presented postoperative complications at the Abel Gilbert Pontón Hospital.Results: The frequency of postoperative complications was 42.5% (n = 20), the female gender predominated in the group with complications, without statistical significance (Group A: 59.3% vs. Group B: 65%). The most frequent age group between the two groups was 56 to 75 years. The greater etiology of both groups was due to acute absences not related to trauma (Group A 96% vs. Group B 90%) and the colon was the most affected organ in the surgeries performed with a greater presentation in Group B without statistical significance ( Group A 52% vs. Group B 70%).
Keywords: ostomies; complications